Análise química e físico-química do tucupi de áreas rurais da região metropolitana de Macapá, Santana e Mazagão - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá)
Tucupi is a product widely consumed in the cuisine of the northern population of Brazil, especially between the states of Pará and Amapá, and in Amapá consumption is very moderate. In their production process crushed and pressed cassava and flour producers remove a liquid called manipueira, from which tucupi and starch are extracted. The preparation of this by-product (flour) is made as follows: the broth is placed in buckets and kept for 24 hours, the starch is separated by decantation and the tucupi goes to boiling being conducive for consumption, where spices are added like salt and garlic. The need to quantify the physicochemical parameters of this fermentation process is due to the high concentration of naturally produced hydrocyanic acid (HCN) during the process. Ingestion of this fluid without proper care can cause serious problems to human health. The following chemical and physicochemical parameters analyzed were: pH, titratable acidity index, humidity, ash content, density, protein and metal quantification (Ca, Fe, Cu, Mn, Mg, Zn and K), however, for To obtain these data, the Adolfo Lutz Institute Analytical Standards were followed
Keywords: Tucupi; Mandioca; Propriedades físico-químicas; Análise química; Análise físico-química; CNPQ::CIENCIAS EXATAS E DA TERRA::QUIMICA